The Relationship Between Hypertension and Body Mass Index (BMI) Among Police Officers Aged 30–60 Years at the Pasuruan Police Resort - Abadi, Vania Zemima Rahmadya; Sunaryati, Titiek; Sugeng, Maria Widjianti (Sean Institute, 2025)
Hypertension is one of the most common non-communicable diseases, often occurring without clear symptoms, making early detection difficult. One of the risk factors contributing to the occurrence of hypertension is an increase in Body Mass Index (BMI). Individuals with high BMI, particularly those categorized as overweight or obese, tend to have a higher risk of developing high blood pressure. This study aims to determine the relationship between hypertension and BMI among police officers aged 30 to 60 years, considering that this profession involves high levels of stress and workload, which can also impact cardiovascular health. The research employed a cross-sectional design with a total of 60 respondents. Data analysis was conducted using the Chi-Square test. The results showed a significant relationship between hypertension and BMI (p = 0.000), where the majority of respondents with hypertension had BMI values classified as overweight or obese. Therefore, regular monitoring of body weight and blood pressure is highly recommended, especially for high-risk professions such as police officers, to prevent more serious health complications in the future.